1983
DOI: 10.1111/j.1471-4159.1983.tb08130.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Tyrosine Hydroxylase System in Rat Brain Slices Using High-Performance Liquid Chromatography with Electrochemical Detection

Abstract: A new method for the measurement of tyrosine hydroxylase (TH; EC 1.14.16.2) activity in brain slices was developed by using high-performance liquid chromatography (HPLC) with electrochemical detection (ED). To estimate TH activity in brain slices containing all of the components of the enzyme system, tetrahydrobiopterin, dihydropteridine reductase, and TH itself, slices were incubated with NSD-1055, an inhibitor of aromatic L-amino acid decarboxylase, and 3,4-dihydroxyphenylalanine (DOPA) formed from endogenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…These findings support the validity of the DOPA assay for measuring tyrosine hydroxylase activity in synaptosomes. Similar conclusions regarding the validity of using the DOPA assay for monitoring tyrosine hydroxylase activity have been presented for in vivo brain measurements (Carlsson et al, 1972) and for in vitro assays of adrenal pheochromocytoma cells (Erny et al, 1981), superior cervical ganglion preparations (Ip et al, 1982), and, more recently, brain slices (Hirata et al, 1983).…”
Section: Egta (Mm)supporting
confidence: 54%
“…These findings support the validity of the DOPA assay for measuring tyrosine hydroxylase activity in synaptosomes. Similar conclusions regarding the validity of using the DOPA assay for monitoring tyrosine hydroxylase activity have been presented for in vivo brain measurements (Carlsson et al, 1972) and for in vitro assays of adrenal pheochromocytoma cells (Erny et al, 1981), superior cervical ganglion preparations (Ip et al, 1982), and, more recently, brain slices (Hirata et al, 1983).…”
Section: Egta (Mm)supporting
confidence: 54%
“…The prevention of the conversion of L-DOPA to dopamine by NSD-1055 and NSD-1055-induced decrease in the tissue content of dopamine, as a result of decrease in newly synthesized dopamine, show that adequate concentrations of the drug were used. (Hirata et al, 1983).…”
Section: Resultsmentioning
confidence: 99%
“…However, in the present experiments we found that the same lower concentration of L-DOPA as that of dopamine inversely facilitated the release of noradrenaline. Hence, we further investigated whether or not L-DOPA produces biphasic actions via presynaptic regulatory mechanisms on the release of noradrenaline and dopamine in the absence and presence of pbromobenzyloxyamine (NSD-1055), a DOPA-decarboxylase inhibitor (Hirata et al, 1983). Part of this work was presented at the Ninth Annual Meeting of Japan Neuroscience Society (Goshima et al, 1985b).…”
Section: Introductionmentioning
confidence: 99%
“…, 1963). The activities of phenylalanine hydroxylase (Milstien and Kaufman, 1975) and tyrosine hydroxylase (Hirata et al, 1983) were shown to increase with addition of 6-methyltetrahydropterin to the rat livtr slice system and BPH4 to the rat striatal slice system, respectively. These results suggest that phenylalanine and tyrosine hydroxylases are subsaturating for a cofactor in vivo.…”
Section: Discussionmentioning
confidence: 99%